To solve this problem, you must first write your equation
Equation:
2x+3=4(x−1)
Step 1: Simplify both sides of the equation.
2x+3=4(x−1) ... Original equation
2x+3=(4)(x)+(4)(−1) ... Distribute
2x+3=4x+(−4
) ... Answer to above
2x+3=4x−4 ... Getting rid of parenthesis
Step 2: Subtract 4x from both sides.
2x+3−4x=4x−4−4x ... Getting rid of 4x
−2x+3=−4 ... When you got rid 4x
Step 3: Subtract 3 from both sides.
−2x+3−3=−4−3 ... Getting rid of 3 so we have x=y
−2x=−7 ... When you got rid of 3
Step 4: Divide both sides by -2.
-2x/-2=-7/-2 ... Divide by 2
Step 5: Answer
x=7/2
So the answer is x=7/2 or 3.5